Estudio comparativo del delito de cohecho activo transnacional en el derecho penal peruano y español - Armendariz Ochoa, Luis Fernando (2025)
This study critically and comparatively examines the characteristic aspects of the crime of active transnational bribery, considering its treatment in the regulations of Peru and Spain. In this context, from a criminological and historical approach to the fight against global corruption, but with special emphasis on Spanish criminal legal doctrine, we seek to contribute to its analysis and improvement. With this purpose, various proposals for regulatory reform will be presented for the current classification of active transnational bribery,among which the incorporation of a legal definition of the term “foreign public official or member of an international body” and the classification of a modalityof active transnational bribery, not exclusively linked to economic objectives, stand out. Finally, the criminal responsibility of legal entities in relation to the crime of international bribery will be addressed, emphasizing the essential requirements for correct accusation and, as a priority, the justification of their criminal sanction.